Knowledge and practice of pharmacy students regarding the use of skin whitening product - Ab. Hadi, Hazrina; Awadh, Ammar Ihsan Jawad (Elsevier Inc., 2015)
OBJECTIVES: The aim of this study was to assess the knowledge and practice of International Islamic University Malaysia (IIUM) Kuantan Undergraduate Pharmacy students on the use of skin whitening product. METHODS: A self-administered questionnaire on the use of skin whitening product was distributed to IIUM Kuantan Undergraduate Pharmacy students at IIUM Kuantan Malaysia. RESULTS: Three hundred and nine (309) of four hundred (400) students responded (77% response rate). The highest percentage of participants is from year three students which is 33.3% while year four students are the least which is 18.8%. The mean of knowledge score, regardless of their year of study is 6.75 over 14. Among the user and non-user of skin whitening products, user shows higher mean knowledge score which is 7.5041 than non-user which is 6.2527.Of the participants, 39.8% (123/309) are using the skin whitening products. 90.8% (108/119) of the respondent read the instruction of the products before using them. CONCLUSIONS: It is proven that the user of skin whitening products has better knowledge about the product than the non-user. Half of the participants are still practicing poor practice in using the skin whitening products. There is a need to educate the students about the proper usage of skin whitening products to avoid any misuse of these products.